JURIDICAL REVIEW OF UNILATERAL ENGAGEMENT ANNULMENT AS AN UNLAWFUN ACT IN CONNECTION WITH CODE OF CIVIL LAW (CASE STUDY OF DECISION NUMBER 45/Pdt.G/2019/PN.Sng) - Yustya Laraswati; Yuniar Rahmatiar; Muhamad Abas (Justisi: Jurnal Ilmu Hukum, 2023)
According to Al-Hamdani, engagement is a man's request for another person's daughter or a woman who is under someone's guardianship, as an introduction before marriage. Engagement as a planned action is undeniable that it can be canceled for that action. The problems raised in this study are how the unlawful act in canceling a unilateral engagement according to the Civil Code and how the judge's considerations in lawsuit No. 45/Pdt.G/2019/PN.Sng. The purpose of this study is to find out how the cancellation of the engagement is said to be an unlawful act and to see the judge's considerations in granting the lawsuit Number: 45/Pdt.G/2019/PN.Sng. The research method used is a qualitative research method. Using a normative juridical approach and using data analysis methods, legal reasoning is problematic. The results of this study show that, in the decision of case No.45/Pdt.G/2019/PN.Sng, the judge considered that: unilateral cancellation of engagement categorized as unlawful acts is correct, in accordance with Article 1365 of the Civil Code. The Defendant unilaterally cancelled the engagement with the Plaintiff which has violated the norms of decency and decency in society.